Achieving Insertion‐Like Capacity at Ultrahigh Rate via Tunable Surface Pseudocapacitance. Issue 12 (9th February 2018) - Zhai, Teng; Sun, Shuo; Liu, Xiaojing; Liang, Chaolun; Wang, Gongming; Xia, Hui
Abstract: The insertion/deinsertion mechanism enables plenty of charge‐storage sites in the bulk phase to be accessible to intercalated ions, giving rise to at least one more order of magnitude higher energy density than the adsorption/desorption mechanism. However, the sluggish ion diffusion in the bulk phase leads to several orders of magnitude slower charge‐transport kinetics. An ideal energy‐storage device should possess high power density and large energy density simultaneously. Herein, surface‐modified Fe2 O3 quantum dots anchored on graphene nanosheets are developed and exhibit greatly enhanced pseudocapacitance via fast dual‐ion‐involved redox reactions with both large specific capacity and fast charge/discharge capability. By using an aqueous Na2 SO3 electrolyte, the oxygen‐vacancy‐tuned Fe2 O3 surface greatly enhances the absorption of SO3 2− anions that majorly increase the surface pseudocapacitance. Significantly, the Fe2 O3 ‐based electrode delivers a high specific capacity of 749 C g −1 at 5 mV s −1 and retains 290 C g −1 at an ultrahigh scan rate of 3.2 V s −1 . With a novel dual‐electrolyte design, a 2 V Fe2 O3 /Na2 SO3 //MnO2 /Na2 SO4 asymmetric supercapacitor is constructed, delivering a high energy density of 75 W h kg −1 at a power density of 3125 W kg −1 . Abstract : Tunable chemical adsorption of redox anions is achieved by surface‐modified Fe2 O3 quantum dots anchored on graphene nanosheets, exhibiting greatly enhanced pseudocapacitance via fast dual‐ion‐involved redox reactions and fast charge/discharge capability. Significantly, the electrode achieves a high capacity up to 749 C g −1 in the Na2 SO3 electrolytes and retains 290 C g −1 at an ultrahigh scan rate of 3.2 V s −1 .